The Effect of Learning Motivation and Vocabulary Mastery towards Students’ Writing Skill in Argumentative Text at Private Senior High School in Kabupaten Serang - Sayyid Khairunas; RIZKY MIRANI DESI PRATAMA; ARY ISWANTO (Wanastra: Jurnal Bahasa dan Sastra, 2019)
The purpose of this study was to determine the effect of learning motivation and vocabulary mastery of the argument text writing skills of students, the influence of learning motivation of the argumentative text writing skills of students, the influence of vocabulary on the argumentative text writing skills of students.This study used survey method. The subjects were all students of class XII in private senior high school in Kabupaten Serang. Data was collected by distributing a questionnaire and giving examination to writing. The data analysis was conducted using descriptive statistics, Pearson's correlation coefficient, coefficient of determination and regression analysis. Statistical test using the T test and F test study was conducted in November 2015 - January 2016.The results showed: (1) there is a significant effect of vocabulary mastery and learning motivation towards writing skills of argumentative English text. This is proven by the Sig = 0.018 < 0.05 and 7.749 Fμ, (2) there is a significant influence on the vocabulary skills of argumentative English text. This is proven by the Sig value by 0.008 < 0.05 and 3.953 tμ, (3) there is a significant influence on the learning motivation towards writing skills of argumentative English text. This is shown by the Sig value 0.004 <0.05 and tμ 5.288.